Transcriptional Responses of Dictyostelium discoideum Exposed to Different Classes of Bacteria - Lamrabet, Otmane; Melotti, Astrid; Burdet, Frédéric; Hanna, Nabil; Perrin, Jackie; Nitschke, Jahn; Pagni, Marco; Hilbi, Hubert; Soldati, Thierry; Cosson, Pierre (Frontiers in Microbiology, 2020)
Dictyostelium discoideum amoebae feed by ingesting bacteria, then killing them in phagosomes. Ingestion and killing of different bacteria have been shown to rely on largely different molecular mechanisms. One would thus expect that D. discoideum adapts its ingestion and killing machinery when encountering different bacteria. In this study, we investigated by RNA sequencing if and how D. discoideum amoebae respond to the presence of different bacteria by modifying their gene expression patterns. Each bacterial species analyzed induced a specific modification of the transcriptome. Bacteria such as Bacillus subtilis, Klebsiella pneumoniae, or Mycobacterium marinum induced a specific and different transcriptional response, while Micrococcus luteus did not trigger a significant gene regulation. Although folate has been proposed to be one of the key molecules secreted by bacteria and recognized by hunting amoebae, it elicited a very specific and restricted transcriptional signature, distinct from that triggered by any bacteria analyzed here. Our results indicate that D. discoideum amoebae respond in a highly specific, almost non-overlapping manner to different species of bacteria. We additionally identify specific sets of genes that can be used as reporters of the response of D. discoideum to different bacteria.